2013
DOI: 10.1371/journal.pone.0071725
|View full text |Cite
|
Sign up to set email alerts
|

ESBL-Producing Enterobacteriaceae: Occurrence, Risk Factors for Fecal Carriage and Strain Traits in the Swiss Slaughter Cattle Population Younger than 2 Years Sampled at Abattoir Level

Abstract: During the past decade extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae have become a matter of great concern in human and veterinary medicine. In this cross-sectional study fecal swabs of a geographically representative number of Swiss cattle at slaughterhouse level were sampled i) to determine the occurrence of ESBL producing Enterobacteriaceae in the Swiss slaughter cattle population younger than 2 years, and ii) to assess risk factors for shedding ESBL producing Enterobacteriaceae. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 18 publications
8
39
6
Order By: Relevance
“…Therefore, the growth of the isolates on the extendedspectrum β-lactam-supplemented medium suggested that they might have produced ESBLs. ESBL-resistant enterobacteria isolation prevalence of 24.2% recorded in this study is higher than 8.4% prevalence of ESBLproducing Enterobacteriaceae reported by Reist et al (2013) in calves slaughtered in Switzerland. Isolation of three genera (Klebsiella, E. coli and Salmonella) of ESBL-resistant enterobacteria in this study, suggested that there could have been acquisition/transfer of genes encoding for ESBLs production by/among the enterobacterial organisms (Schmeidel et al, 2014).…”
Section: Discussioncontrasting
confidence: 72%
“…Therefore, the growth of the isolates on the extendedspectrum β-lactam-supplemented medium suggested that they might have produced ESBLs. ESBL-resistant enterobacteria isolation prevalence of 24.2% recorded in this study is higher than 8.4% prevalence of ESBLproducing Enterobacteriaceae reported by Reist et al (2013) in calves slaughtered in Switzerland. Isolation of three genera (Klebsiella, E. coli and Salmonella) of ESBL-resistant enterobacteria in this study, suggested that there could have been acquisition/transfer of genes encoding for ESBLs production by/among the enterobacterial organisms (Schmeidel et al, 2014).…”
Section: Discussioncontrasting
confidence: 72%
“…This prevalence rate was slightly higher than a study in Switzerland which reported 8.4% among calves in a slaughter house, but in contrast to a study in South-West Nigeria which reported an absence of ESBL genes among isolates from bovine fecal specimens from slaughter houses (Reist et al, 2013;Inwezerua et al, 2014). The observation shows that the prevalence of ESBL producers in animals is on the rise and may pose risk to humans (Chantziaras et al, 2014).…”
Section: Discussioncontrasting
confidence: 74%
“…Thus, only a few studies have looked into the prevalence and risk factors for ESBLPE carriage in cattle (5,6). A valid comparison of prevalence and risk factors for ESBLPE carriage between countries is very difficult even in human studies, due to the vast differences in the populations and the methodologies of the different studies (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of antimicrobials has often been suggested to be the main culprit for this phenomenon (4), there are in fact no studies that have looked into this question. Moreover, the data regarding other risk factors for carriage of ESBL-producing Enterobacteriaceae (ESBLPE) in livestock in general and cattle in particular are limited to those from the analysis of only a few factors (5,6). Also, although molecular analysis of these isolates has been reported, such data have never been used for the analysis of the dissemination dynamics of ESBLPE in and between farms.…”
mentioning
confidence: 99%